2014 IEEE International Symposium on Information Theory 2014
DOI: 10.1109/isit.2014.6874817
|View full text |Cite
|
Sign up to set email alerts
|

Side-information in control and estimation

Abstract: Abstract-As in portfolio theory, we can think of the value of side-information in a control system as the change in the "growth rate" due to side-information. A scalar counterexample (motivated by carry-free deterministic models) shows the value of side-information for control does not exactly parallel the value of side-information for portfolios. Mutual-information does not seem to be a bound here.The concept is further explored through a spinning vector control system that is re-oriented at each time so that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Many previous works around parameter uncertainty in control systems highlight the importance of the controller to plan and have worked towards developing an understanding of the "value of information in control" [24]- [29]. More recent work has examined the importance of side-information in control problems [6], [8], [30]- [33].…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous works around parameter uncertainty in control systems highlight the importance of the controller to plan and have worked towards developing an understanding of the "value of information in control" [24]- [29]. More recent work has examined the importance of side-information in control problems [6], [8], [30]- [33].…”
Section: A Related Workmentioning
confidence: 99%
“…The impact of parameter uncertainty in control and estimation is highlighted by the intermittent Kalman filtering model [1], [2] and related works on dropped control packets [3]- [7]. In particular, these works show how critical the ability to plan is for control systems -while the critical erasure probability for estimation in the intermittent Kalman filtering setting depends only on the maximal eigenvalue of the system, the critical erasure probability of the dual problem with dropped controls depends on the product of all eigenvalues -thus control can tolerate far less uncertainty than estimation [8]. This makes intuitive sense, since a controller must commit to an action at every timestep without knowledge of the future, whereas the observer in the estimation problem can revisit its decisions in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental limits for control and estimation of systems over both noiseless rate-limited channels [45], [46] and noisy channels [47] have been established. A series of works [48]- [50] established the limits of control and estimation over packet dropping networks and it was recently shown that control and communication co-design could provide unbounded performance gains in such settings [51].…”
Section: Control and Communication Co-designmentioning
confidence: 99%
“…Indeed, the right hand side of (2.2) denotes the information generating speed of the LTI system [8,23], which is generating information about the unknown initial system state. This resemblance also motivated researchers to study control systems from the perspective of information theory, e.g., see [24][25][26][27][28][29][30][31][32][33][34].…”
Section: Control Over Communication Channels 221 Control Over Noisementioning
confidence: 99%